Optimization of removal of Cr by γ-alumina nano-adsorbent using response surface methodology - Dubey S.; Upadhyay S.N.; Sharma Y.C. (My University, 2025)
This study explores the applicability of Box–Behnken design matrix and response surface methodology (RSM) for removal of chromium (VI) over γ-alumina nanoparticles in designing the experiments to evaluate the interactive effects of the three most important process variables namely, pH (2.0–10.0), adsorbent dose (0.2–1.0 mg/l) and initial concentration of metal ions (5–25 ppm) on the removal. The optimal conditions for the three effective parameters, thus identified, were found to be: pH 2.03, initial metal concentration 5 ppm, adsorbent dose 0.9170 g/50 ml with the desirability score of 1.00. Langmuir isotherm and pseudo-second-order model were ascertained to be more appropriate for the process of removal. The process of Cr removal by nano-alumina was feasible, exothermic and spontaneous in nature. The response surface methodology provided important information on interactions between the factors and is recommended for similar adsorption systems. © 2016